"I feel reassured, but there is no guarantee." How do women with a future childbearing desire respond to active surveillance of cervical intraepithelial neoplasia grade 2? A qualitative study. (5th April 2022) - Hansen, Joan; Kirkegaard, Pia; Folmann, Birgitte; Bungum, Helle Folge; Hammer, Anne
Abstract: Introduction: In Denmark, women with a future childbearing desire diagnosed with cervical intraepithelial neoplasia grade 2 (CIN2) are recommended active surveillance instead of excisional treatment. However, we have limited and contradictory knowledge about how active surveillance of CIN2 may affect women emotionally. The aim of this study was to explore thoughts and emotional responses in women undergoing active surveillance of CIN2 and to explore how active surveillance may affect women's future childbearing desire. Material and methods: This qualitative study was conducted in the gynecological outpatient clinic, the Department of Obstetrics and Gynecology, Gødstrup Hospital, Denmark. Women of childbearing age undergoing active surveillance with colposcopy, biopsy and smear every 6 months due to CIN2 were eligible for enrollment. In‐depth semi‐structured interviews were conducted. The interviews were audiotaped and transcribed verbatim. A thematic analysis was performed using a phenomenological approach. Results: A total of 20 women were included. All women experienced nervousness and anxiety when they were diagnosed with CIN2 initially. Their main concern was whether they had cancer. Most women carried on with their everyday lives with only minor occasional worries about CIN2, often prompted just before check‐up. However, some women were particularly nervous and found the period between check‐ups frustrating and challenging. Women did not want to postpone their plans for pregnancy because of CIN2, but experienced the worries and check‐ups associated with active surveillance as disruptive elements in their family planning. Women preparing for fertility treatment had their startup unnecessarily delayed due to active surveillance of CIN2, as clinical guidelines were inconsistent across subspecialties. Various factors influenced women's emotional well‐being: life circumstances, information needs, and mental and physical discomfort during colposcopic examination. Conclusions: Women felt that worries and check‐ups due to active surveillance of CIN2 were disrupting elements in their family planning, although they did not affect their every‐day life. Some women, however, were particularly anxious, demonstrating the importance of including women's experiences and preferences in clinical counseling. The fact that fertility treatment was delayed due inconsistent guidelines across subspecialties, suggests a need for a revision of current guidelines.